Comparison of the Quality of Written Scientific Arguments in Different Laboratory Environments - Kapici, Hasan Ozgur; Akcay, Hakan; Koca, Ece Ebrar (SPRINGER, 2022)
Although physical hands-on laboratory experiments are commonly used in schools, virtual laboratory environments are also being used in science classrooms. Their possibilities and impact on students' achievement, conceptual understanding, and inquiry skills have been investigated by other researchers. Yet, it is difficult to find studies about the effect of virtual learning environments on written argumentation in science classrooms. In the current study, the influence of hands-on and virtual laboratories on pre-service science teachers' scientific writing was investigated using the science writing heuristic. The participants were 52 pre-service science teachers who were assigned to two conditions. One group used the hands-on laboratory to design and implement experiments and used a paper-based worksheet to write their arguments; the other group did their investigations through a computer-based virtual-tool laboratory and wrote their arguments on the online learning platform. Pre-service science teachers' written arguments were evaluated using content analysis. The findings revealed that the overall quality of written arguments created by pre-service science teachers in both laboratory environments was at an intermediate level. Furthermore, pre-service science teachers who learned in the virtual laboratory posed better testable questions, presented strong and valid evidence, and used multiple representations better than their counterparts in the hands-on laboratory. An important conclusion of the current study is that the science writing heuristic can be used effectively in both virtual and hands-on laboratory environments.
Keywords: Argumentation; Hands-on laboratory; Science writing heuristic; Virtual laboratory; STUDENTS QUESTIONS; SCIENCE; INQUIRY; LEARN; SIMULATIONS; SCAFFOLDS; EDUCATION; MIDDLE; Education & Educational Research